B‐Cell Receptor‐Associated Protein 31 Regulates Human Embryonic Stem Cell Adhesion, Stemness, and Survival via Control of Epithelial Cell Adhesion Molecule. (October 2014) - Kim, Won‐Tae; Seo Choi, Hong; Min Lee, Hyun; Jang, Young‐Joo; Ryu, Chun Jeih
Abstract B‐Cell receptor‐associated protein 31 (BAP31) regulates the export of secreted membrane proteins from the endoplasmic reticulum (ER) to the downstream secretory pathway. Previously, we generated a monoclonal antibody 297‐D4 against the surface molecule on undifferentiated human embryonic stem cells (hESCs). Here, we found that 297‐D4 antigen was localized to pluripotent hESCs and downregulated during early differentiation of hESCs and identified that the antigen target of 297‐D4 was BAP31 on the hESC‐surface. To investigate the functional role of BAP31 in hESCs, BAP31 expression was knocked down by small interfering RNA. BAP31 depletion impaired hESC self‐renewal and pluripotency and drove hESC differentiation into multicell lineages. BAP31 depletion hindered hESC proliferation by arresting cell cycle at G0/G1 phase and inducing caspase‐independent cell death. Interestingly, BAP31 depletion reduced hESC adhesion to extracellular matrix (ECM). Analysis of cell surface molecules showed decreased expression of epithelial cell adhesion molecule (EpCAM) in BAP31‐depleted hESCs, while ectopic expression of BAP31 elevated the expression of EpCAM. EpCAM depletion also reduced hESC adhesion to ECM, arrested cell cycle at G0/G1 phase and induced cell death, producing similar effects to those of BAP31 depletion. BAP31 and EpCAM were physically associated and colocalized at the ER and cell surface. Both BAP31 and EpCAM depletion decreased cyclin D1 and E expression and suppressed PI3K/Akt signaling, suggesting that BAP31 regulates hESC stemness and survival via control of EpCAM expression. These findings provide, for the first time, mechanistic insights into how BAP31 regulates hESC stemness and survival via control of EpCAM expression. Stem Cells2014;32:2626–2641